(untitled) (Research, Society and Development, 2021)
Worldwide, obesity and overweight grew to become a public health concern, raising some awareness in physical activity about slimming or lean mass gain. Several strategies have been utilized to maximize the preservation of lean mass, one of being the inclusion of tonics that improve the protein synthesis, resulting in a positive protein balance, wich leads to hypertrophy and strength growth. Reaching the aimed weight loss, and to sustain it, is a very difficult task; it’s necessary to take into consideration the genetic facts, the metabolics, environmental, behavioral and cultural of the individual. Aging is a process that causes wearness and progressive irreversible changes in our vast body sistem. Therefore, the focus in this report aimed the investigation about the use of Creatine and Whey Protein on the healthy elderly public that also practice physical activity. The current report, refers it self to a bibliophiled integrated review, wich analyzes that, the Creatine supplying raised significantly the fat-free mass in response to the resistance training, resulting in a lower body fat range. The ingestion of the Whey Protein assisted the growth in muscular mass, strength and induced a raise in the skeletal muscle mass protein, concluding that the Whey Protein is more efficient in aiding the retention of the skeleton muscle, in women, than the collagen protein.